2012
DOI: 10.5923/j.fph.20120205.03
|View full text |Cite
|
Sign up to set email alerts
|

Food Additives in Products for Children Marketed in Brazil

Abstract: Studies show children suffer fro m adverse effects to food additives, in both acute and chronic forms. Children are among the biggest consumers of processed products and have more susceptibility to these adverse effects. In Brazil, there are few data about the exposure to food additives. Therefore, the objective of this article is to elaborate a database of food additives present in products for children. Th is database was built fro m August 2010 to October 2010 fro m the nutritional information on products f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Similarly, the same additives were reported within the cereal children products in Brazil. 4 Analysis of our results showed that certain categories of food items contain more food additives than the others, table 4. A large number of food additives are present in biscuits and cakes (n=25), crisps (n=23), and dairy and meat products (n=18) compared with other food categories.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, the same additives were reported within the cereal children products in Brazil. 4 Analysis of our results showed that certain categories of food items contain more food additives than the others, table 4. A large number of food additives are present in biscuits and cakes (n=25), crisps (n=23), and dairy and meat products (n=18) compared with other food categories.…”
Section: Discussionmentioning
confidence: 79%
“…2 The acceptable daily intake of food additives (ADI) is the amount of a food additive (expressed on a bodyweight basis), which can be ingested daily during an entire lifetime without appreciable health risk. 3 The study conducted in Brazil by Lorenzoni et al 4 showed that 506 products were classified as children products, from which 92% of these products contained information on their ingredients (and additives) and 86.5% of these studied products contained at least one additive in their formulation. The most used additives were lecithin (45.30%) and citric acid (22.86%) and artificial dyes Allura red (9.83%), tartrazine (6.84%), and 5.77% for both sunset yellow or brilliant blue.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant ascorbic acid and citric acid were prevalent in pureed baby foods and most commonly added in nutritive foods were flavors, emulsifiers (lecithin) and thickener (carrageenan and guar gum). The similar study revealed that the most additives used in processed foods were lecithin, citric acid and artificial dyes 32 .…”
Section: Food Additivesmentioning
confidence: 76%
“…No Brasil, refrigerantes, bebidas industrializadas à base de frutas (em embalagem longa vida ou em pó), salgadinhos, doces, chocolates, embutidos, pães e biscoitos estão entre os alimentos mais consumidos por crianças [7][8][9][10][11][12][13][14][15][16] . Esses alimentos usualmente contêm quantidades expressivas de açúcar, gordura e sódio [17][18][19][20][21] , e muitos deles apresentam aditivos alimentares [22][23][24] , além de, com frequência, suas embalagens apresentarem estratégias de marketing direcionadas ao público infantil 25 .…”
Section: Introductionunclassified